Pengaruh Strategi Pemasaran Digital, Kualitas Produk dan Harga terhadap Keputusan Pembelian Konsumen pada Produk Aksesoris Manik-Manik - Maharani Ikaningtyas; Syafa Gading Adhip Arafa; Ajeng Suta Mayangsari; Fitria Ayu Kartika D; Luthfi Nurul Mubayyinah; Ahmad Harris Akbar; Santika Purwaty Ningsih (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
This study aims to analyze the influence of digital marketing strategies, product quality, and pricing on consumer purchasing decisions in the context of bead accessories. Utilizing a qualitative approach through literature review, the research synthesizes findings from previous studies published between 2019 and 2024. The results indicate that digital marketing strategies especially those involving social media, visual content, and e-commerce platforms significantly shape consumer preferences and purchasing decisions. Additionally, product quality, including durability, aesthetics, and unique design, plays a crucial role in fostering consumer trust and loyalty. Pricing is also a key determinant, where the perceived value-to-cost ratio greatly influences consumers’ final buying choices. This research contributes to the understanding of consumer behavior within the creative handmade accessory industry and offers practical implications for small business owners in designing more effective marketing strategies.